Preparation method of irradiation phase change electrolyte matched with lithium iron phosphate positive electrode material

CN122931006APending Publication Date: 2026-10-16RES INST OF CHEM DEFENSE PLA ACAD OF MILITARY SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610826088.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但其配套液态碳酸酯电解液存在三大瓶颈:易泄漏燃烧、高温易分解产气、低温黏度剧增,与LiFePO4正极材料界面副反应导致Fe溶出,严重制约安全与寿命

Benefits of technology

1)以低黏度的电解液态前驱体(聚醚丙烯酸酯、碳酸酯增塑剂、锂盐)灌注LiFePO4电池,经γ/电子束辐照原位自由基交联,液态向固态化相变。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931006A_ABST
    Figure CN122931006A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of batteries, and specifically discloses an irradiation phase change electrolyte matched with a lithium iron phosphate positive material and a preparation method thereof. The application adds acrylonitrile monomers and pentaerythritol tetraacrylate monomers into an electrolyte to prepare a precursor electrolyte, and the precursor electrolyte is irradiated by gamma rays or an electron beam to be in-situ cross-linked and solidified, so that the irradiation phase change electrolyte is prepared. The application does not need an initiator, is uniformly solidified at room temperature, has excellent interface contact, has high ionic conductivity and anti-lithium dendrite ability, and the obtained electrolyte matches a lithium metal battery of a lithium iron phosphate positive electrode. ‑1 The capacity retention rate of the lithium metal battery reaches 92.3% at 5 C rate after 1000 cycles, the ionic conductivity at room temperature is as high as 7.68 mS cm , the interface impedance is significantly reduced, the safety and cycle life of the battery are effectively improved, and a practical solution is provided for a high-safety long-life lithium iron phosphate-based lithium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology, specifically relating to a method for preparing an irradiated phase change electrolyte adapted to lithium iron phosphate cathode material. Technical Background Lithium iron phosphate (LiFePO4) batteries have become the mainstream choice for power batteries and energy storage due to their advantages such as long cycle life, good thermal stability, and low cost. However, the accompanying liquid carbonate electrolyte has three major bottlenecks: easy leakage and combustion, easy decomposition and gas generation at high temperatures, and a sharp increase in viscosity at low temperatures. These electrolytes also cause Fe dissolution through interfacial side reactions with the LiFePO4 cathode material, which seriously restricts safety and lifespan. Although traditional solid-state / gel electrolytes are safe, they have high interfacial impedance, low ionic conductivity, and difficulty in in-situ wetting of porous LiFePO4 electrodes. Thermal / UV-initiated polymerization requires initiator residues, results in uneven curing, and has poor penetration, making it unsuitable for the large-scale production of LiFePO4 batteries.

[0002] Therefore, it is necessary to develop technologies that can balance liquid wettability and solid-state safety to provide key solutions for high-safety, long-life LiFePO4 batteries. Summary of the Invention

[0003] The purpose of this invention is to develop an electrolyte preparation method adapted to lithium iron phosphate cathode materials, and to synthesize an irradiated phase change electrolyte adapted to lithium iron phosphate cathode materials to improve their cycle and safety performance.

[0004] The technical solution adopted in this invention is as follows: In a first aspect, the present invention provides a method for preparing an irradiated phase change electrolyte adapted to lithium iron phosphate cathode material, comprising the following steps: S1 Preparation of precursor solution: Add nitrile monomers and acrylate monomers to the electrolyte solvent containing lithium salts, and stir to mix evenly; The mass ratio of the nitrile monomer to the acrylate monomer is 1:5 to 5:1; The nitrile monomers are one or a mixture of two or more selected from acrylonitrile, methacrylonitrile, N,N-diethylcyanoacrylamide, and 2-butenonitrile; the acrylate monomers are one or a mixture of two or more selected from trimethylolpropane triacrylate, cyanurate triacrylate, pentaerythritol tetraacrylate, and 1,6-hexanediol diacrylate. S2 Irradiation Phase Change: The precursor solution obtained in step S1 is irradiated with γ-rays or an electron beam to induce polymerization of the monomers and obtain the irradiated phase change electrolyte. The irradiation absorbed dose rate is 10-120 Gy / min, and the absorbed dose is 0.1-10 kGy. Preferably, the lithium salt is one or a mixture of two or more of lithium hexafluorophosphate, lithium dioxalatoborate, lithium tetrafluoroborate, lithium bis(difluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide. Furthermore, the lithium salt is lithium hexafluorophosphate, the concentration of the lithium salt in the electrolyte is 0.5~2 mol / L, and the stirring time is 2-6 h.

[0005] Preferably, the electrolyte solvent is a carbonate solvent, and the selection range includes: ethylene carbonate (EC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC).

[0006] Preferably, in step S1, the nitrile monomer and the acrylate monomer are acrylonitrile and pentaerythritol tetraacrylate, respectively, with mass concentrations of 20~60 g / L and 20~60 g / L, respectively.

[0007] Preferably, in step S2, the radiation source that generates γ rays is... 60 Co source or 137 Cs source; the electron beam is generated by an electron accelerator with an energy of 0.1~10 MeV.

[0008] Preferably, step S2 irradiation is in-situ irradiation, specifically: after injecting the precursor solution into a battery with lithium iron phosphate as the positive electrode and lithium metal as the negative electrode, the battery is irradiated.

[0009] Secondly, the present invention provides an electrolyte adapted to lithium iron phosphate cathode material, which is prepared by the method described in the first aspect.

[0010] Thirdly, the present invention provides a lithium-ion battery, wherein the active material of the positive electrode of the lithium-ion battery is lithium iron phosphate, and the electrolyte is the irradiated phase change electrolyte described in the second aspect.

[0011] Furthermore, the lithium-ion battery uses a lithium sheet as the negative electrode.

[0012] Furthermore, the lithium-ion battery separator uses Celgard2500.

[0013] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) A LiFePO4 battery is filled with a low-viscosity electrolyte precursor (polyether acrylate, carbonate plasticizer, lithium salt), and then crosslinked in situ by γ / electron beam irradiation to achieve a phase transition from liquid to solid state.

[0014] 2) This technology is initiator-free, has strong penetration, and cures rapidly and uniformly at room temperature, perfectly filling the pores of the LiFePO4 electrode. It exhibits excellent interfacial contact and high conductivity (10). -3 S / cm).

[0015] 3) Cross-linked networks suppress leakage and resist dendrite formation, solving the safety and interface pain points of LiFePO4 batteries. Attached Figure Description

[0016] Figure 1 Optical spectra of irradiated phase change electrolytes before and after irradiation.

[0017] (a) and (b) are photographs of the precursor electrolyte and the irradiated phase change electrolyte, respectively.

[0018] Figure 2 Ionic conductivity tests of irradiated phase change electrolytes at different temperatures.

[0019] A is 1000 / T, and the unit is K. -1 B is ln σ, and the unit is S cm. -1 .

[0020] Figure 3 A lithium metal half-cell assembled with an irradiated phase change electrolyte and lithium iron phosphate as the cathode material is shown in the long-cycle performance diagram at 5 C rate.

[0021] A represents the number of cycles, B represents the specific capacity in mAh / g, and C represents the coulombic efficiency in %.

[0022] Figure 4 An irradiated phase change electrolyte was used to assemble a lithium metal half-cell with lithium iron phosphate as the cathode material. Impedance diagrams of the battery after 1 cycle and 1000 cycles at 5 C rate were obtained.

[0023] The horizontal axis represents the real part, with the unit being Ω, and the vertical axis represents the imaginary part, also with the unit being Ω. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0026] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0027] Example 1 An irradiated phase change electrolyte adapted to lithium iron phosphate cathode material is prepared by the following method: 1) Preparation of irradiated phase change electrolyte precursor electrolyte: Add acrylonitrile monomer (0.12 g) and pentaerythritol tetraacrylate monomer (0.18 g) to an electrolyte containing lithium hexafluorophosphate (1.0 M LiPF6 in EC:DEC=1:1, of which there is 10.0 vol% FEC) (10 g), and stir to mix evenly; 2) Irradiation phase change: The phase change electrolyte precursor electrolyte is irradiated with γ-rays at an absorbed dose rate of 30 Gy / min and an absorbed dose of 3 kGy. After irradiation, the electrolyte is dried to obtain the irradiated phase change electrolyte.

[0028] like Figure 1 The image shows the optical spectrum of the irradiated phase change electrolyte prepared in this invention. (a) is the electrolyte precursor solution before irradiation, and (b) is the phase change electrolyte after irradiation. The phase change electrolyte forms a solid state, proving the successful preparation of the irradiated phase change electrolyte.

[0029] like Figure 2 The figure shows the ionic conductivity tests of the irradiated phase change electrolyte at different temperatures. The tests show that it exhibits a high ionic conductivity of 7.68 mS / cm at room temperature. -1 It is superior to most electrolytes. Its high ionic conductivity is conducive to the rapid transport of lithium ions in the electrolyte, thereby improving its rate performance.

[0030] For the irradiated phase change electrolyte assembled lithium metal battery of the present invention, the positive electrode material is lithium iron phosphate. The assembled battery is irradiated with gamma rays at an absorbed dose rate of 30 Gy / min, with an absorbed dose of 3 kGy, for in-situ polymerization. Then, it is tested using an electrochemical testing system at 2.5-4.0 V, 5 C rate, and 25 °C. Figure 3 As shown, the battery can reach 102 mAh g during its first discharge at 5C. -1 The discharge specific capacity still maintains 92.3% capacity retention after 1000 cycles at 5 C rate, demonstrating excellent charge-discharge cycle stability and excellent electrochemical performance.

[0031] For the irradiated phase change electrolyte assembled lithium metal battery of this invention, the positive electrode material is lithium iron phosphate. Its impedance after 1 cycle and 1000 cycles at a high rate of 5 C was tested using an electrochemical workstation. Figure 4As shown, the impedance curves of the battery with irradiated phase change electrolyte matched with lithium iron phosphate cathode material are compared, and the impedance characteristics after the first cycle and after 1000 cycles are shown. After 1000 long cycles, the interfacial impedance of the battery decreased from 175 Ω to 66 Ω relative to the first cycle. The significant decrease in impedance indicates that the interfacial side reactions between the irradiated phase change electrolyte and the lithium iron phosphate cathode were effectively suppressed, and the interfacial structure maintained good stability during long cycling. This result directly proves that the phase change electrolyte reduces interfacial side reactions and forms a good interface during long cycling, providing a key interfacial guarantee for the battery to achieve long cycle life.

[0032] Example 2 Using 0.03 g of acrylonitrile and 0.27 g of pentaerythritol tetraacrylate from step 1) of Example 1, and with other conditions the same as in Example 1, the resulting irradiated phase change electrolyte retained 81.4% of its capacity and had an ionic conductivity of 5.83 mS / cm after 1000 cycles at 5 C. -1 .

[0033] Example 3 Using 0.06 g of acrylonitrile and 0.24 g of pentaerythritol tetraacrylate from step 1) of Example 1, and with other conditions the same as in Example 1, the resulting irradiated phase change electrolyte exhibited a capacity retention of 84.6% and an ionic conductivity of 6.77 mS / cm after 1000 cycles at 5 C. -1 .

[0034] Example 4 Using 0.09 g of acrylonitrile and 0.21 g of pentaerythritol tetraacrylate from step 1) of Example 1, and with other conditions the same as in Example 1, the resulting irradiated phase change electrolyte exhibited a capacity retention of 88.5% and an ionic conductivity of 7.15 mS / cm after 1000 cycles at 5 C. -1 .

[0035] Example 5 Using 0.15 g of acrylonitrile and 0.15 g of pentaerythritol tetraacrylate from step 1) of Example 1, and with other conditions the same as in Example 1, the resulting irradiated phase change electrolyte retained 85.9% of its capacity and had an ionic conductivity of 6.91 mS / cm after 1000 cycles at 5 C. -1 .

[0036] Example 6 Using 0.2 g of acrylonitrile and 0.3 g of pentaerythritol tetraacrylate from step 1) of Example 1, and with other conditions the same as in Example 1, the resulting irradiated phase change electrolyte exhibited a capacity retention of 81.1% and an ionic conductivity of 5.62 mS / cm after 1000 cycles at 5 C. -1 .

[0037] Example 7 Using 0.28 g of acrylonitrile and 0.42 g of pentaerythritol tetraacrylate from step 1) of Example 1, and with other conditions the same as in Example 1, the resulting irradiated phase change electrolyte exhibited a capacity retention of 79.6% and an ionic conductivity of 5.34 mS / cm after 1000 cycles at 5 C. -1 .

[0038] Example 8 Using 0.36 g of acrylonitrile and 0.54 g of pentaerythritol tetraacrylate from step 1) of Example 1, and with other conditions the same as in Example 1, the resulting irradiated phase change electrolyte retained 76.4% of its capacity and had an ionic conductivity of 4.69 mS / cm after 1000 cycles at 5 C. -1 .

[0039] Example 9 The absorbed dose in step 2) of Example 1 was changed to 4 kGy, while other conditions remained the same as in Example 1. The resulting irradiated phase change electrolyte retained 90.1% of its capacity and had an ionic conductivity of 7.22 mS / cm after 1000 cycles at a 5 C rate. -1 .

[0040] Example 10 The absorbed dose in step 2) of Example 1 was changed to 5 kGy, while other conditions remained the same as in Example 1. The resulting irradiated phase change electrolyte retained 86.0% of its capacity and had an ionic conductivity of 6.94 mS / cm after 1000 cycles at a 5 C rate. -1 .

[0041] Example 11 The absorbed dose in step 2) of Example 1 was changed to 6 kGy, while other conditions remained the same as in Example 1. The resulting irradiated phase change electrolyte retained 84.3% of its capacity and had an ionic conductivity of 6.78 mS / cm after 1000 cycles at a 5 C rate. -1 .

[0042] Example 12 The absorbed dose in step 2) of Example 1 was changed to 7 kGy, while other conditions remained the same as in Example 1. The resulting irradiated phase change electrolyte retained 83.3% of its capacity and had an ionic conductivity of 6.41 mS / cm after 1000 cycles at a 5 C rate. -1 .

[0043] Example 13 The absorbed dose in step 2) of Example 1 was changed to 8 kGy, while other conditions remained the same as in Example 1. The resulting irradiated phase change electrolyte retained 81.9% of its capacity and had an ionic conductivity of 6.02 mS / cm after 1000 cycles at a 5 C rate. -1 .

[0044] Example 14 The absorbed dose in step 2) of Example 1 was changed to 9 kGy, while other conditions remained the same as in Example 1. The resulting irradiated phase change electrolyte retained 80.9% of its capacity and had an ionic conductivity of 5.67 mS / cm after 1000 cycles at a 5 C rate. -1 .

[0045] Example 15 The absorbed dose in step 2) of Example 1 was changed to 10 kGy, while other conditions remained the same as in Example 1. The resulting irradiated phase change electrolyte retained 79.1% of its capacity and had an ionic conductivity of 5.32 mS / cm after 1000 cycles at a 5 C rate. -1 .

[0046] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Those skilled in the art can make various modifications to the technical solutions in the embodiments based on the above description. It is neither necessary nor possible to exhaustively describe all possible implementations. Any modifications, variations, substitutions, etc., made based on the technical content disclosed in this invention are equivalent to equivalent implementations and should be included within the protection scope of this invention.

Claims

1. A method for preparing an irradiated phase change electrolyte adapted to lithium iron phosphate cathode material, characterized in that, Includes the following steps: S1 Preparation of precursor solution: Add nitrile monomers and acrylate monomers to the electrolyte solvent containing lithium salts and mix thoroughly; The mass ratio of the nitrile monomer to the acrylate monomer is 1:5 to 5:1; The nitrile monomers are one or a mixture of two or more selected from acrylonitrile, methacrylonitrile, N,N-diethylcyanoacrylamide, and 2-butenonitrile; the acrylate monomers are one or a mixture of two or more selected from trimethylolpropane triacrylate, cyanurate triacrylate, pentaerythritol tetraacrylate, and 1,6-hexanediol diacrylate. S2 Irradiation Phase Change: The precursor solution obtained in step S1 is irradiated with γ-rays or an electron beam to induce polymerization of the monomers and obtain the irradiated phase change electrolyte. The irradiation absorbed dose rate is 10-120 Gy / min, and the absorbed dose is 0.1-10 kGy.

2. The method for preparing an irradiated phase change electrolyte adapted to lithium iron phosphate cathode material according to claim 1, characterized in that, The lithium salt is one or a mixture of two or more of lithium hexafluorophosphate, lithium dioxaborate, lithium tetrafluoroborate, lithium bis(difluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.

3. The method for preparing an irradiated phase change electrolyte adapted to lithium iron phosphate cathode material according to claim 2, characterized in that, The lithium salt is lithium hexafluorophosphate, and the concentration of the lithium salt in the electrolyte is 0.5~2 mol / L.

4. The method for preparing an irradiated phase change electrolyte adapted to lithium iron phosphate cathode material according to claim 1, characterized in that, In step S1, the nitrile monomer and the acrylate monomer are acrylonitrile and pentaerythritol tetraacrylate, respectively, with mass concentrations of 10~60 g / L and 10~60 g / L, respectively.

5. The method for preparing an irradiated phase change electrolyte adapted to lithium iron phosphate cathode material according to claim 1, characterized in that, In step S2, the radiation source that generates γ rays is 60 Co source or 137 Cs source; the electron beam is generated by an electron accelerator with an energy of 0.1~10 MeV.

6. The method for preparing an irradiated phase change electrolyte adapted to lithium iron phosphate cathode material according to claim 1, characterized in that, The electrolyte solvent is a carbonate solvent.

7. The method for preparing an irradiated phase change electrolyte adapted to lithium iron phosphate cathode material according to claim 1, characterized in that, The irradiation in step S2 is in-situ irradiation, specifically: after injecting the precursor solution into a battery with lithium iron phosphate as the positive electrode and lithium metal as the negative electrode, the battery is irradiated.

8. An electrolyte adapted to lithium iron phosphate cathode material, prepared by the method described in any one of claims 1 to 7.

9. A lithium-ion battery, characterized in that, The active material of the positive electrode of the lithium-ion battery is lithium iron phosphate, and the electrolyte is the irradiated phase change electrolyte as described in claim 8.

10. The lithium-ion battery according to claim 9, characterized in that, The lithium-ion battery uses lithium foil as the negative electrode; the lithium-ion battery separator is a polypropylene separator.